Respuesta :

Answer:

(2,-4)

Step-by-step explanation:

Answer:

It is C)  (x − 1)^2 + (y + 3)^2 = 4

Step-by-step explanation:

The radius is the distance between the center and the point on the circle.

Center: (1, −3); Point: (1, −1)

Distance formula: d =  square root of {(x2 - x1)^2 + (y2 - y1)^2}

r = square root of  {(1 − 1)^2 + (−1 + 3)^2 }

r =  square root of {0 + 4 } = 2

(x − h)^2 + (y − k)^2 = r2 ----> (x − 1)^2 + (y + 3)^2 = 4

Hope this isn't confusing and helps. I also know its right because I just did this on USA Testprep.

ACCESS MORE